Architectures de résistance ordinaire. Une méthode hybride pour transformer une cité avec ses habitants - Marion Howa; Éric Chauvier (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This reflection explores how the self-constructions leaded by residents in social housing are practices of ordinary resistance. How can these experiences be taken seriously in an architectural transformation project? This combined look between anthropology and architecture proposes to recount the experiments carried out in the research project for the rehabilitation of the city of Beutre (Mérignac, France). The historical processes of informal work are integrated into the project. With multiple resident tactics, the architects experimented an open design, where their intervention adapts to each singular cases, between due repair and free self-construction. To reflect the hybridity of knowledge of architectural transformation, the text combines multiple materials in the form of a field notebook (interviews, drawings, photographs).